The scientific revolution of Thomas S. Kuhn and its contribution to the conflict resolution paradigm in Indonesia - Mohammad Takdir; Masykur Arif (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2022)
The development of science which is reflected by the paradigm shift and the scientific revolution must be able to find new ideas more progressively. This study is motivated by the significance of a paradigm shift in the development of science through discoveries that are useful for the needs of human life. This study aims to explain Thomas Kuhn’s epistemological views of the scientific revolutions which have become important issues in his thinking and their implications for society’s perspective on conflict paradigms. This article uses a qualitative method to describe Thomas Kuhn’s scientific revolution affects social change in society. This study is classified as library research with the individual life history approach. This article shows that Kuhn’s thought has been implicated significantly in all scientific disciplines, including the conflict resolution paradigm. Kuhn’s thoughts can change the community’s perspective or paradigm of conflict resolution models from a security and law approach to local wisdom. In addition, Kuhn’s thoughts have changed the meaning of peace, namely from negative peace to positive peace in people’s lives. This study concluded that one of the important contributions of Kuhn’s thinking of the paradigm shift and scientific revolution is the development of conflict resolution and religious peacebuilding in society.